Comparative study of elbow disorders in young high-performance gymnasts - Dexel, J.; Marschner, K.; Beck, H.; Platzek, I.; Wasnik, S.; Schuler, M.; Nasreddin, A.; Kasten, P. (International Journal of Sports Medicine, 2014)
The study aimed to investigate the prognosis of osteochondral affection (e. g., osteochondritis dissecans (OCD), cartilage lesions, fractures and bone edema in the elbows of high-performance gymnasts (n=30) compared to prognosis results with athletes not undergoing excessive stress on the upper extremity (n=29). The study also tested a novel isotropic 3D-FSE-sequence (CUBE) technique as an early diagnostic modality. Standard protocol was used to conduct the MRI examinations, which were then compared to results from the CUBE - sequence. The gymnast group (p=0.012) presented a significantly higher prevalence of complaints in the elbow joint compared to the other athlete group. Furthermore, osteochondral lesions in MRIs appeared more frequently in the group of gymnasts (n=10, 33%, p=0.033), including 7 cases (23%) of OCD. In the control athlete group 2 asymptomatic cases of OCD and one case of bone edema were detected. The MRI investigation with the CUBE - sequence showed similar results as the standard MRI protocol in terms of the diagnosis sensitivity. The current study indicates that juvenile gymnasts are at a higher risk for osteochondral lesions of the elbow than athletes without excessive stress on the upper extremities.